2013
DOI: 10.1188/13.onf.575-580
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to Implementing Cancer Survivorship Care Plans

Abstract: Purpose/Objectives To evaluate the process of survivorship care plan (SCP) completion and to survey oncology staff and primary care physicians (PCPs) regarding challenges of implementing SCPs. Design Descriptive pilot study. Setting Two facilities in Vermont, an urban academic medical center and a rural community academic cancer center. Sample 17 oncology clinical staff created SCPs, 39 PCPs completed surveys, and 58 patients (breast or colorectal cancer) participated in a telephone survey. Methods Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
132
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(145 citation statements)
references
References 8 publications
6
132
0
7
Order By: Relevance
“…The time required to find information and complete the ISCP was, however, comparable to that reported in many studies (Curcio, Lambe, Schneider, & Khan, 2012;Dulko et al, 2013;Stricker et al, 2011). The length of the meeting during which the ISCP was provided was also similar to that of other studies (Curcio et al, 2012;Stricker et al, 2011), although one study reported a shorter time (between 15 and 30 minutes; Salz et al, 2014).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The time required to find information and complete the ISCP was, however, comparable to that reported in many studies (Curcio, Lambe, Schneider, & Khan, 2012;Dulko et al, 2013;Stricker et al, 2011). The length of the meeting during which the ISCP was provided was also similar to that of other studies (Curcio et al, 2012;Stricker et al, 2011), although one study reported a shorter time (between 15 and 30 minutes; Salz et al, 2014).…”
Section: Discussionsupporting
confidence: 80%
“…Studies have documented the development of an ISCP for women with breast cancer (Clausen et al, 2012;Dulko et al, 2013;Smith, Singh-Carlson, Downie, Payeur, & Wai, 2011), for survivors of colorectal cancer (Baravelli et al, 2009;Salz et al, 2012), and for other types of cancer (Mayer, Gerstel, Leak, & Smith, 2012) based on existing ISCPs. Some recommend personalizing the ISCP to better meet the complex needs of survivors (Haq et al, 2013).…”
mentioning
confidence: 99%
“…Several studies have focused on what scps should entail [8][9][10][11][12][13] , their rationale and strategies for their implementation 14,15 , or obstacles to their completion 10,[15][16][17][18][19][20] . Other studies have described the perspectives of patients about, and patient and health care provider support for or satisfaction with, scps [21][22][23][24][25][26][27][28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the difficulty of clarifying the roles and responsibilities of each team member in terms of filling out and delivering the IFCP has been raised, as have the lack of time for customized development and implementation, and the lack of resources (staff and financial) (Brennan et al, 2014;Dulko et al, 2013).…”
Section: Anticipated Barriers To Implementationmentioning
confidence: 99%
“…The use of an electronic format is recommended, as is giving a paper copy to the survivor at the last treatment. As discussed in other studies (Baravelli et al, 2009;Dulko et al, 2013), the nurse would be the professional appointed to complete and deliver the IFCP near the end of treatment or shortly thereafter (Mayer, Gerstel, Leak, & Smith, 2012). An end-oftreatment meeting would normalize the transition to survivorship at the end of active treatment, introduce the IFCP as an information and coordination tool, respond to questions raised, direct to resources where necessary, and encourage the transition to the family physician (Jefford et al, 2011).…”
Section: Specifying the Content And Format Of The Ifcp And The Time Omentioning
confidence: 99%